Research on rapid construction technology of three-dimensional safety control area for the complex maintenance work environment of substation. Issue 1 (1st January 2023) - An, Xing; Zhang, Xiao-hua; Liu, Zhan; Yang, ShunFu; Sun, Bo
Abstract: According to the actual needs of the substation operation and maintenance team, this paper studies the defect video intelligent analysis technology in realizing three-dimensional cross-border early warning, analyzes the principle and early warning application of narrowband millimeter-wave technology and develops a set of 3D cross-border early warning system for substation maintenance operation. The system adopts wideband network technology to realize the remote operation and stable data transmission between the system and the warning and analysis service software of mobile terminal. In this early warning analysis system, this study uses the combination of intelligent video analysis and millimeter-wave radar dynamic target capture to solve many deficiencies in early warning accuracy by relying solely on intelligent video analysis and early warning. Through the on-site verification of the test system, the system's overall function is consistent with the substation maintenance and maintenance requirements. It is simple to use, and the accuracy of the crossover warning reaches more than 85%.